ANALISIS KEMAMPUAN LITERASI PADA MATERI TEKS DESKRIPSI DI KELAS IV SD NEGERI 104203 BANDAR KHALIPAH - Al Hilal Hamdi Rambe; Dian Armanto; Anita Yus (STKIP Subang, 2026)
This study aims to analyze students' literacy skills in descriptive text materials in Grade IV at SD Negeri 104203 Bandar Khalipah. Literacy is a basic ability that includes reading, understanding, and writing information effectively. The research method used is qualitative descriptive. The research subjects consisted of 28 fourthgrade students. Data collection techniques were carried out through observation, tests, and documentation. The results of the study show that students' literacy skills are in the sufficient category, with some students able to understand the content of descriptive texts, but still experiencing difficulties in identifying structures and writing descriptive texts systematically. Factors affecting literacy skills include reading interest, learning methods, and the availability of learning media. This study concludes that innovative learning strategies are needed to improve students' literacy skills, especially in descriptive text materials. Keywords: Literacy, Descriptive Text, Elementary School.